MEDIA PEMBELAJARAN INFORMATIKA BERUPA SLIDESGO DAN VIDEO UNTUK MENINGKATKAN HASIL BELAJAR POROGAPIT SISWA SEKOLAH DASAR NEGERI KALISEGORO KELAS III (Adi Widya: Jurnal Pendidikan Dasar, 2023)
In the study conducted at SD Negeri Kalisegoro with a total of 20 students. The goal of this research is to improve learning outcomes of porogapit material in 3rd Grade students of SD Negeri Kalisegoro through the application of informatics-based learning media, especially with slidesgo and videos. The learning media that used have been tested by material experts and media experts. There are several stages on this research, namely (1) Design; (2) Observation; (3) Implementation of Actions; and (4) Evaluation. This study used pretest and posttest instruments. The results showed an increase of 2.2% grade average from an average score of 88.5 to 90.5 and satisfactory learning outcomes were achieved. The application of slidesgo and video learning media is proven to increase student understanding of division using the pogapit method and students understanding of learning questions in the form of stories.